A diverting quarter century? Evidence-based police-led diversion 25 years on - Neyroud, Peter (International journal of police science & management, 2024)
It is more than 25 years since Lawrence Sherman delivered his ‘Ideas in American Policing’ lecture on ‘evidence-based policing’ for the US Police Foundation. The original work [Sherman LW (1998) Evidence-Based Policing. Ideas in American Policing. Washington, DC: Police Foundation], Sherman’s equally seminal study on ‘preventing crime’ [Sherman LW, Gottfredson D, MacKenzie D, et al. (1997) Preventing Crime: What Works, What Doesn’t, What’s Promising. Washington, DC: Office of Justice Programs] and the subsequent development of evidence-based policing in the ‘Triple T’ [Sherman LW (2013) The rise of evidenced-based policing: targeting, testing and tracking. In: Tonry M (ed.) Crime and Justice in America 1975–2025. Chicago: University of Chicago Press] have been immensely influential as well as, for some, controversial. In 1998, Sherman challenged scholars, practitioners and policymakers to use the ‘best available evidence’ to guide policy and practice. He then posed four questions: ‘What is it? What is new about it? How does it apply to a specific example of police practice? How can it be institutionalized?’. Taking the lead from Sherman's questions, this contribution to the 25-year anniversary collection focuses on one example – police-led diversion – to illustrate the development and challenges of institutionalizing evidence-based policing since 1998.